Hodnocení finanční situace podniku a návrhy na její zlepšení - Tran Ngoc, Toan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Bakalářská práce se zabývá zhodnocením finanční situace společnosti UNIVERS s. r. o. za období 2011-2015. Práce je rozdělena do tří hlavních částí. První část obsahují teoretické poznatky, které jsou následně využity v praktické části. Ke zhodnocení finanční situace společnosti jsou použity vybrané metody finanční analýzy. Poslední část práce je věnováno vlastním návrhům, které by měly dopomoci ke zlepšení finanční situace.

The bachelor thesis deals with the assessment of the financial situation in the company UNIVERS s. r. o. during years 2011-2015. The thesis is divided into three basic parts. The first part provides the theoretical basis, which is subsequently used in the practical part. The chosen methods of the financial analysis are used in order to evaluate the financial situation of the above-mentioned company. In the last part, I present my own proposals, which could improve the company financial situation.
Evaluation of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: Finanční analýza; rozvaha; výkaz zisku a ztráty; cash flow; likvidita; SWOT analýza; Financial analysis; balance sheet; profit and lost statement; cash flow; liquidity; SWOT analysis